Heuristic optimization of impeller sidewall gaps-based on the bees algorithm for a centrifugal blood pump by CFD. - Onder, Ahmet; Incebay, Omer; Sen, Muhammed Arif; Yapici, Rafet; Kalyoncu, Mete (International Journal of Artificial Organs, 2021)
Optimization studies on blood pumps that require complex designs are gradually increasing in number. The essential design criteria of centrifugal blood pump are minimum shear stress with maximal efficiency. The geometry design of impeller sidewall gaps (blade tip clearance, axial gap, radial gap) is highly effective with regard to these two criteria. Therefore, unlike methods such as trial and error, the optimal dimensions of these gaps should be adjusted via a heuristic method, giving more effective results. In this study, the optimal gaps that can ensure these two design criteria with The Bees Algorithm (BA), which is a population-based heuristic method, are investigated. Firstly, a Computational Fluid Dynamics (CFD) analysis of sample pump models, which are selected according to the orthogonal array and pre-designed with different gaps, are performed. The dimensions of the gaps are optimized through this mathematical model. The simulation results for the improved pump model are nearly identical to those predicted by the BA. The improved pump model, as designed with the optimal gap dimensions so obtained, is able to meet the design criteria better than all existing sample pumps. Thanks to the optimal gap dimensions, it has been observed that compared to average values, it has provided a 42% reduction in aWSS and a 20% increase in efficiency. Moreover, original an approach to the design of impeller sidewall gaps was developed. The results show that computational costs have been significantly reduced by using the BA in blood pump geometry design.